Jaanhvi Forest a Miracle of People's Participation in Forest Management and Environment Protection - Misra, Kamal (Journal of Soil and Water Conservation, 2022)
Participatory or joint forest management is recently an officially sponsored and patronised concept mid state and site specific models are being implemented at different places. The system was however, a natural evolution at manv sites where community living did not die completely. Jaanhvi village experience in Damodar valley area is one such experience. It is a fore runner of what is now being seen every where. The renewable produce have started flowing from the protected area such as fuel (5000 qt1./year); timber (100 m3/yr.); poles (300/yr.); leaf (20 head loads/day during the season), datun (250 qtl/yr.) besides grazing of abundantly growing grass.